DEMOKRATISASI DAN PROBLEM NETRALITAS BIROKRASI DI INDONESIA - Gde Wisura (Jurnal Manajemen Kepegawaian, 2008)
This article will explain the problematic situations of bureaucratic reform in Indonesia. The fall of new orde rezim showed how well the process of democratic spread to all parts of Indonesia. Civil society tried to create and reconstruct the political system based on principles of demokratic rule, including how to make bureaucratic independenly. In fact, many case in reform era found there is political cooptation in the bureaucratic system.Keywords : Political cooptation, democratization, civil servants